If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 10 = 14 + 3n Reorder the terms: 10 + 2n = 14 + 3n Solving 10 + 2n = 14 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 10 + 2n + -3n = 14 + 3n + -3n Combine like terms: 2n + -3n = -1n 10 + -1n = 14 + 3n + -3n Combine like terms: 3n + -3n = 0 10 + -1n = 14 + 0 10 + -1n = 14 Add '-10' to each side of the equation. 10 + -10 + -1n = 14 + -10 Combine like terms: 10 + -10 = 0 0 + -1n = 14 + -10 -1n = 14 + -10 Combine like terms: 14 + -10 = 4 -1n = 4 Divide each side by '-1'. n = -4 Simplifying n = -4
| 8x/9=1/2 | | 3x^3/4=-24 | | 3.236(5.3m-7.9)-1.9m=65.369 | | ax-c=N | | 2a+14a+-11a=-15 | | -10x^2-18x=0 | | 9/17=3/a | | 99=11x | | 99=-6g | | t+2t-2t=8 | | 31=44-p | | -2(-y-5)-7(4y-7)=y+5+3y | | -5y+20=-5y | | =325*-7 | | x+3-4=3(5+4) | | 21=3/8n | | 4(x-2)+3=25 | | y=4(-3)+8 | | 9x-3x(x-5)=6x+3 | | 13/20/1/6 | | (8x^3-28x^2)-(10x+35)= | | 1.9(7.766x-6.71)=66.9302 | | 5-11=33 | | -5(y-4)=-3y+8y | | (-15/36)*x^2 | | 5/6(y)-3/4(y)=-3 | | m-m+5m-4m=13 | | 6x+2-4(x+5)=18 | | 3+4*5x=67 | | 3v^2+11v+6=0 | | 11+5n=-2(-n+5)+6(2n+3) | | -2+6(-6m-5)=4 |